KEMISKINAN URBAN DALAM NOVEL SEPORSI MIE AYAM SEBELUM MATI KARYA BRIAN KHRISNA - Karuniawan, Dwiky Yoga (Universitas Hamzanwadi, 2025)
The aim of this research is to describe the forms of poverty, the categorization of poverty, and the factors that cause poverty in urban society as depicted in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna. This study employs a descriptive analytical method. The research data consist of sentences in the novel that contain elements of poverty. The data source is the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna. The data collection technique used is the observation and note-taking method. Data analysis is conducted using content analysis techniques combined with the literary sociology approach. The results of the study reveal forms of poverty in urban society as represented in the novel, including weak economic conditions, inadequate housing infrastructure, and slum environmental conditions. Furthermore, the study identifies the categorization of poverty into structural and cultural poverty. The factors causing urban poverty in the novel include limited job opportunities, low human resource capacity, and misfortune within the social structure.